Estudio de la degradación del Cianuro utilizando peróxido de hidrógeno en los efluentes del proceso de cianuración de la empresa Minesadco S.A Ubicada en el sitio el Pache, Cantón Portovelo, Provincia de El Oro, 2014. - Ortega Maldonado, Dévora Gianella (2015)
In this research we worked with effluents area cyanidation company Minesadco SA, laboratory scale through a filter of ion exchange resins and then a stirred reactor by adding hydrogen peroxide and a catalyst sulfate penta hydrated copper. The initial operating conditions were kept constant (resin amount and the contact time, agitation, pH 11.5 and the initial concentration of free cyanide 137.07 ppm) .The 3 treatments applied in various concentrations of excess H2O2 75%, 100% and 125% three reaction times 10,15 and 20 min, was used for the experimental tests the 2 x 3 factorial arrangement (two factors and three levels for each factor) making a total of 27 trials. 500ml samples of each test for analysis of remaining free CN volumetric silver nitrate and potassium iodide was collected (averaging three tests for each sample volumes)